Synthesis and Structural Studies on Transition Metal Complexes Derived from 4-Hydroxy-4-methyl–2-pentanone-1H-benzimidazol-2-yl-hydrazone - M. Neelamma; P. Venkateswar Rao; G. H. Anuradha (E-Journal of Chemistry)
Transition metal complexes of Cr(III), Fe(III), Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) with a tridentate ligand, 4-hydroxy-4-methyl-2-pentanone-1H-benzimidazole-2yl-hydrazone (H-HPBH) derived from the condensation of 2-hydrazinobenzimidazole and diacetone alcohol was synthesized. Characterization has been done on the basis of analytical, conductance, thermal and magnetic data, infrared, 1H NMR, electronic, mass and ESR spectral data. From analytical and thermal data, the stoichiometry of the complexes has been found to be 1:1 (metal: ligand). Divalent complexes have the general formula [M(HPBH)Cl(H2O)2] in octahedral geometry, [M(HPBH)Cl] in tetrahedral and square planar stereochemistries and trivalent complexes [M(HPBH)Cl2(H2O)] in octahedral disposition. Infrared spectral data suggest that the ligand HPBH behaves as a monobasic tridentate ligand with N: N: O donor sequence towards the metal ions. On the basis of the above physicochemical data, octahedral, tetrahedral and square planar geometries were assigned for the complexes. The ligand and metal complexes were screened for their physiological activities against E. coli and S. aureus. The order of physiological activity has been found to be Cu(II) > Ni(II) > Zn(II) > Co(II) > Cr(III) > Mn(II) > Fe (III) > ligand against E.coli and Ni(II) > Cu(II) > Zn(II) > Mn(II) > Cr(III) > Fe(III) > Co(II) > ligand against S. aureus.